2013
DOI: 10.1021/ac403133t
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of Urinary Creatinine by Reactive-Thermal Desorption-Extractive Electrospray-Ion Mobility-Tandem Mass Spectrometry.

Abstract: A direct, ambient ionization method has been developed for the determination of creatinine in urine that combines derivatization and thermal desorption with extractive electrospray ionization and ion mobility-mass spectrometry. The volatility of creatinine was enhanced by a rapid on-probe aqueous acylation reaction, using a custom-made thermal desorption probe, allowing thermal desorption and ionization of the monoacylated derivative. The monoacyl creatinine [M + H]+ ion (m/z 156) was subjected to mass-to-char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…In this paper, we focus on the application of one such approach to organic aerosol analysis, namely extractive electrospray ionisation (EESI) MS. The EESI process predominantly forms molecular ions ([M + H] + and [M − H] − ) and is able to efficiently ionise organic analytes even in complex sample matrices such as urine (Devenport et al, 2014), beer (Zhu et al, 2010) and olive oil . Doezema et al (2012) demonstrated an initial application of EESI-MS to organic aerosols, identifying a number of products formed from α-pinene ozonolysis in positive ion mode.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we focus on the application of one such approach to organic aerosol analysis, namely extractive electrospray ionisation (EESI) MS. The EESI process predominantly forms molecular ions ([M + H] + and [M − H] − ) and is able to efficiently ionise organic analytes even in complex sample matrices such as urine (Devenport et al, 2014), beer (Zhu et al, 2010) and olive oil . Doezema et al (2012) demonstrated an initial application of EESI-MS to organic aerosols, identifying a number of products formed from α-pinene ozonolysis in positive ion mode.…”
Section: Introductionmentioning
confidence: 99%
“…Modified acetylation of creatinine [9] was carried out in an aqueous media at a temperature more than 100 °C. The boiling point of the derivatized product is less than 100 °C [9], so almost all of the sample vaporized immediately and after extraction with PPy/GO fiber, IMS analysis was performed.…”
Section: Determining the Position Of Ims Peak Of Derivatized Creatininementioning
confidence: 99%
“…The boiling point of the derivatized product is less than 100 °C [9], so almost all of the sample vaporized immediately and after extraction with PPy/GO fiber, IMS analysis was performed.…”
Section: Determining the Position Of Ims Peak Of Derivatized Creatininementioning
confidence: 99%
See 2 more Smart Citations